PENGEMBANGAN SEKTOR PERTANIAN DALAM MENGATASI MASALAH PENGANGGURAN DI KABUPATEN NAGEKEO - Dea, Agnes Yunita; Kaleka, Marten Umbu (Jurnal Pertanian Khairun, 2024)
Unemployment actually occurs due to a lack of job opportunities compared to the number of people looking for work. Some of the actions taken by the Regional Government are conducting job training in collaboration with the East Nusa Tenggara Job Training Center and across provinces. The aim is to improve the skills of the existing workforce in Nagekeo so that they can compete in the labor market. This research was conducted with the aim of knowing employment conditions in Nagekeo Regency, proposing agricultural development to increase income and overcome unemployment. The method used is a literature study using data from BPS and related institutions and analyzed descriptively. The results of the analysis show that: 1) Over 5 years, the labor force participation rate (TPAK) of Nagekeo Regency has shown fluctuation. Several factors can influence fluctuations in labor force participation, such as changes in the size of the labor force, wages, education levels, and economic growth. 2) The agricultural sector is experiencing a good trend and continues to develop, which is a potential and opportunity for the economy of Nagekeo Regency. 3) The principles of agricultural development include increasing investment in agriculture, job training, increasing entrepreneurial abilities, and developing the agricultural industry. Keywords: Development, Agriculture, Unemployment